Analysis of a complex network of financial agents. - Chen, Jonathan Guan Wei. (2009)
Many observations and research in areas of physics have been conducted on financial network. Within the researches, 3 power laws (Pareto wealth distribution, Scalefree network and Self organized criticality) in financial networks are of great interest in areas of physics due to its scale invariant nature. In this thesis, an attempt to build a model of rational interacting merchants in an ideal globalized market and to observed if the model will generate the power-laws observed in real life market(Pareto wealth distribution and scale-free network) and power law (Self-Organized Criticality) proposed by research. The numerical simulation results display the potential of the model to generate power-law-like distribution in wealth and link distribution. Although for model’s result there are no power law for bankruptcy distribution, bankruptcy distribution seems to have 2 long tails on its left and right.